2005
DOI: 10.1530/eje.1.01919
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous 24-h ghrelin secretion pattern in fasting subjects: maintenance of a meal-related pattern

Abstract: Objective: Ghrelin stimulates GH release and causes weight gain through increased food intake and reduced fat utilization. Ghrelin levels were shown to rise in the preprandial period and decrease shortly after meal consumption, suggesting a role as a possible meal initiator. However, ghrelin secretion in fasting subjects has not yet been studied in detail. Design: 24-h ghrelin profiles were studied in six healthy volunteers (three females; 25.5 years; body mass index 22.8 kg/m 2 ) and compared with GH, insulin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
107
3
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(119 citation statements)
references
References 37 publications
(32 reference statements)
6
107
3
3
Order By: Relevance
“…Plasma ghrelin increased on both mornings (around 8:00), the middle of the day (12:00 to 13:00) and in the early evening (17:00 to 19:00), consistent with the expected meal times. These increases were followed by a spontaneous decline in plasma ghrelin despite the fact that the subjects were fasting (Natalucci et al, 2005).…”
Section: A Role For Cephalic Phase Responses In Appetite and Satiety?mentioning
confidence: 99%
“…Plasma ghrelin increased on both mornings (around 8:00), the middle of the day (12:00 to 13:00) and in the early evening (17:00 to 19:00), consistent with the expected meal times. These increases were followed by a spontaneous decline in plasma ghrelin despite the fact that the subjects were fasting (Natalucci et al, 2005).…”
Section: A Role For Cephalic Phase Responses In Appetite and Satiety?mentioning
confidence: 99%
“…The lack of a preprandial ghrelin increase in ad libitum-fed rats was also observed after both groups of rats were food deprived for an equivalent amount of time, suggesting that it was the habituated meal pattern, rather than energy deficit, that was responsible for the ghrelin increase. The limited human data indicate individuals who habitually consume three meals per day exhibit increased ghrelin concentrations around habitual mealtimes followed by a nadir ϳ2 h later (29). This observation suggests that changes in energy status are not required to alter ghrelin profiles and lends additional support for an anticipatory influence on ghrelin secretion.…”
mentioning
confidence: 99%
“…Support for this role is multifold. Intracerebroventricular and intraperitoneal ghrelin injections increase food intake and body weight in rodents (29,43). Additionally, infusion of anti-ghrelin antibodies into the rat brain suppresses fasting-induced feeding.…”
mentioning
confidence: 99%
“…Therefore, to minimize the effects of daily ghrelin dynamics in this study, all cat samples were taken in the early morning and before food. Additionally, the reported amplitudes of ghrelin secretion pulses in humans are usually in the range of 0.5 ± 0.1 ng/mL,26 which therefore could only pose a modest confounding factor, given that the difference between the mean concentration of serum ghrelin before and after radiotherapy in our cats was almost 5‐fold greater (2.4 ng/mL). Specific feline ghrelin physiology research is nevertheless indicated to further evaluate these issues, as well as an assessment of ghrelin stability and ideal storage conditions.…”
Section: Discussionmentioning
confidence: 89%
“…The relatively small differences between before and after radiation ghrelin concentrations could therefore also have been confounded by such unknown natural ghrelin dynamics. For instance, ghrelin is known to be influenced by meals in man 26. Nevertheless, on 24‐hour serial assessment of circulating ghrelin concentrations in humans, it was shown that samples taken before breakfast correlated strongly with 24‐hour integrated area under the curve values ( r  = 0.873), suggesting that a single starved morning sample could be used as a surrogate for 24‐hour profiles to estimate overall ghrelin concentrations 27.…”
Section: Discussionmentioning
confidence: 99%